Adaptation Peculiarities of Early Age Children to a Preschool Education Institution (a Case Study of Kaunas City) - Stoncelyte, Raimonda; Masiliauskiene, Erika (Jaunųjų mokslininkų darbai, 2019)
Adaptation of a child to a preschool education institution is a difficult and troublesome process especially after his experience with parental care. Mother care is advisable for early age children but, due circumstances, parents often decide to enroll a child in a preschool education institution. Parents should prepare for that in advance and later collaborate with teachers. It is no a secret that it is difficult to find time for quality and successful partnership. Nevertheless, both, parents and the education institution, need to understand that they have a common goal - continuous and successful child education. The research results revealed the essential peculiarities of successful adaptation of early age children to a preschool education institution: regular parent-teacher exchange of information about the child‘s well-being, adaptation actions to be used at home and in the education institution seeking to ensure the continuity of educational activities in institutional settings and at home, periodic teacher-parent meetings to discuss adaptation issues, trust between parents and teachers and mutual support.